A new species of Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Pará State, with an updated key to Brazilian species of the robusta group - Magalhães, Oséias Martins; Moreira, Felipe Ferraz Figueiredo; Galvão, Cleber (Zootaxa, 2016)
Rhagovelia brunae Magalhães & Moreira sp. nov., collected in the State of Pará, Brazil, is described, illustrated, and compared with congeners. The new species belongs to the robusta group and can be differentiated from others by the general color black, abdominal sternum VII with black denticles laterally, male hind trochanter with 1–4 subequal spines plus a longer spine, and male hind femur lacking a medium spine between the proximal and distal rows of spines. Additionally, an updated identification key to species of the robusta group occurring in Brazil is presented.